Struggling With Business Corporate Cynical Impression? Powerful Methods of CSR to Enhance Corporate Image and Consumer Purchase Intention - Avotra, Andrianarivo Andriandafiarisoa Ralison Ny; Chengang, Ye; Wei, Xu; Ming, Jiang; Marcelline, Tsimisaraka Raymondo Sandra (Frontiers in Public Health, 2021)
This research focuses on Chinese students' perception about the company’s image and their purchase intention of corporate cycle of population, if the organization has the cynical impression in the minds of its targeted customers. To cop-up with the organizational cynical impression of emerging economies, this study proposed three different types of corporate social responsibility. These types are Economic & Legal CSR, Philanthropic CSR, and Ethical CSR and its effets on the corporate cycle of the population health. This study's main objective is to determine which CSR type is better to reduce the corporate cynical impression on corporate image and consumer purchase intention. In study design, the bootstrap approach and AMOS 24 were employed to deal with mediation. The researchers recruited 500 individuals from different educational institutions in China using a simple random selection process. The outcomes of this study indicate that all three types of corporate social responsibility (CSR) are successful in mitigating the detrimental effects of corporate cynicism on firm image and consumer purchase intentions for population health influencing economies. A more effective technique of boosting a company's corporate image and consumer purchase intention is via charitable CSR, which may help restore the company's image and consumer purchase intention that have been affected by corporate cynicism among its target customers to test the effects of population health in business cycles.